2020
DOI: 10.3389/fphys.2020.616552
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Midkine and Its Potential Pathophysiological Role in COVID-19

Abstract: SARS-CoV2 infection not only causes abnormal severe pneumonia but also induces other relevant pathophysiological effects on several tissues and organs. In this regard, the clinical complications observed in COVID-19 include acute coronary syndrome, pulmonary thromboembolism, myocarditis and, in the severe cases, the occurrence of disseminated intravascular coagulation. Literature on COVID-19 highlighted the central role of the Renin Angiotensin Aldosterone System in the determinism of SARS-CoV2 cellular intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Specifically, epithelial cells are highlighted as the main sender cells in factor 1 (Figure 4a), involving top ranked signals such as APP, MDK, MIF and CD99 (Figure 4b). These molecules were reported to be produced by epithelial cells 2935 and participate in immune cell recruiting 31–33 , in response to mechanical stress in lungs 34 and regeneration of the alveolar barrier during viral infection 35 . Importantly, MDK can exacerbate leukocyte recruitment to sites of inflammation 36 , consistent with the immune response that Tensor-cell2cell deconvolved in severe COVID-19 patients 18,3739 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, epithelial cells are highlighted as the main sender cells in factor 1 (Figure 4a), involving top ranked signals such as APP, MDK, MIF and CD99 (Figure 4b). These molecules were reported to be produced by epithelial cells 2935 and participate in immune cell recruiting 31–33 , in response to mechanical stress in lungs 34 and regeneration of the alveolar barrier during viral infection 35 . Importantly, MDK can exacerbate leukocyte recruitment to sites of inflammation 36 , consistent with the immune response that Tensor-cell2cell deconvolved in severe COVID-19 patients 18,3739 .…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, epithelial cells are highlighted as the main sender cells in factor 1 (Figure 4a), involving top ranked signals such as APP, MDK, MIF and CD99 (Figure 4b). These molecules were reported to be produced by epithelial cells [29][30][31][32][33][34][35] and participate in immune cell recruiting [31][32][33] , in response to mechanical stress in lungs 34 and regeneration of the alveolar barrier during viral infection 35 .…”
Section: Tensor-cell2cell Successfully Associates Differences In Intercellular Communication With Varying Severities Of Covid-19mentioning
confidence: 99%
“…Furthermore, NETs can induce the EMT in lung epithelial cells, thus further supporting NET role in fibrosis pathogenesis (Middleton et al, 2020;Pandolfi et al, 2021;d'Alessandro et al, 2022). So much so that anti-midkine monoclonal antibodies have been proposed as a new potential therapeutic strategies in COVID-19 (Sanino et al, 2020).…”
Section: Role Of Midkine and Netosismentioning
confidence: 94%
“…It has been indicated that overexpression of midkine is associated with several biological processes such as differentiation, proliferation, carcinogenesis, adhesion, migration of cells and survival and it was considered as a heparin-binding growth factor or a cytokine [2] , [3] . Related to these physiological pathways, midkine plays an important role in multiple pathological conditions including inflammation, cancer, injury, autoimmune diseases, and neurodegenerative diseases [1] , [2] , [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Midkine was found to be a physiological mediator of renin angiotensin aldosterone system (RAAS) and it plays an important role in interaction between kidney and lung [9] . It has been shown that RAAS is one of the key factors for the regulation of the migration and proliferation of the smooth muscle cells, the production of extracellular matrix (ECM), the upregulation of the adhesion molecules expression, and the production of proinflammatory cytokines [4] .…”
Section: Introductionmentioning
confidence: 99%